The involvement of individuals with speech and language impairments in research: insights from a co-creation process - Katharina Giordano; Manja Wonschik; Juliane Leinweber (Research Involvement and Engagement)
Abstract Background Involvement of end users in development processes is increasing, but there are still relatively few examples of the involvement of people with speech and language impairment (PWSLI). One reason for this is that these impairments are sometimes seen as a criterion for exclusion. The aim of this article is to identify both opportunities and challenges in a co-created technology development process with PWSLI. The project HiSSS (Hybrid and interactive speech and language therapy after stroke) has the objective of developing a hybrid teletherapy application for the treatment of speech and language impairments following a stroke. It includes a co-creation development process, engaging people with speech and language impairments and speech and language therapists. A comprehensive evaluation of the co-creation process in the HiSSS project will highlight opportunities and challenges in a co-created technology development process with PWSLI.All affiliations are captured correctly Methods The data sources (workshop transcripts, process adaptations, team meeting protocols, researchers' reflective notes) from the co-creation process were analysed using Braun and Clarke's reflexive thematic analysis (2021). Both challenges and opportunities were identified deductively through the analysis. In a further step, the authors inductively generated themes to which they assigned the opportunities and challenges. Results Six workshops with a total of 11 speech and language therapists and four workshops with a total of 7 people with speech and/or language impairments took place. Through thematic analysis four themes were generated: (1) Communicative limitations, (2) Researcher skills, (3) Interprofessional collaboration, (4) Organisation of participation. Conclusions The generated themes represent dimensions of co-creation that should be considered in future technology developments. This study demonstrates the complexity of technology co-creation with PWSLI and confirms that they can be effectively involved in research and contribute meaningfully to technology development. Whether and to what extent users should be involved in research projects must be clarified as early as possible and on a case-by-case basis according to the specific objectives of the respective project. In order to take these four dimensions into account in future co-creation projects, the funding conditions must provide the necessary framework. Trial registration The study is registered in the German Register of Clinical Trials (DRKS00030430).